Network pharmacology and molecular dynamics simulation reveal antineoplastic potential of Antarctic sponge-derived suberitenones - Bhowmik, Prasenjit; Mallick, Rahul; Duttaroy, Asim K. (Frontiers in Chemistry, 2025)
IntroductionMore than a thousand new marine natural products have been isolated each year over the past ten years, and compared to synthetic compounds, the success ratio of approved marine drugs to the total number of reported potential marine natural products is extremely high. In a recent in vitro cytotoxicity test, 11 suberitenones–a class of oxidized sesterterpenes–were identified and shown to have low levels of cytotoxicity. This study focuses on the investigation of the anti-neoplastic ability of of these suberitenones through different in silico analysis.MethodsThe study uses a variety of computational techniques, including quantitative structure–activity relationship (QSAR), ADMET, prediction of activity spectra for substances (PASS) prediction, network pharmacology, molecular docking, and molecular dynamics simulation.Results and discussionThe molecular docking showed that Suberitenone I, Secosuberitenone A, and Suberitenone J exhibited higher binding affinity of - 8.9, -9.4, and -8.8 kcal/mole against CASP3, MAPK3, and EGFR respectively which is further supported by molecular dynamics simulation analysis and can be considered for in vitro and in vivo investigation as potential antineoplastic agents.